Platform Capitalism and Its Discontents: Labor Precarity and Resistance Strategies among Ride-Hailing Drivers in Indonesia - Patricia González; Jorge García; Andrea Vargas (Journal of Social Science Utilizing Technology, 2026)
Background. This research examines the phenomenon of platform capitalism and its implications on labor precarity, focusing on ride-hailing drivers in Indonesia. The rise of digital platforms has revolutionized labor markets worldwide, yet it has also exacerbated the precariousness of work, especially in the gig economy. This study investigates how ride-hailing drivers navigate the challenges posed by platform capitalism, particularly concerning their labor rights, income security, and work conditions. Purpose. The research aims to explore the strategies of resistance employed by drivers to combat exploitation and negotiate for better working conditions. Method. The study employs a qualitative research design, utilizing in-depth interviews with ride-hailing drivers in major Indonesian cities to collect empirical data. Results. The findings reveal that while drivers experience significant labor precarity, including low pay, irregular work hours, and lack of social security, they actively resist through collective actions, advocacy for regulation, and negotiation with platforms. These resistance strategies reflect an emerging form of labor activism in the digital economy. Conclusion. The study concludes that despite the challenges of platform capitalism, there is potential for drivers to foster solidarity and advocate for structural reforms that address labor exploitation within the gig economy.